Penerapan Metode Permainan Bingo untuk Meningkatkan Aktivitas Belajar dalam Pembelajaran Kosa Kata Benda Bahasa Inggris Kelas 4 Sekolah Dasar - Nur Fitriani Dewi; Devidescu Cristiana Victoria; Ike Anita (Fakultas Keguruan dan Ilmu Pendidikan Universitas Langlangbuana, 2019)
English vocabulary is the beginning of learning English, English vocabulary is very much to be understood. By using the correct English vocabulary we can communicate or make a sentence properly and correctly. So, better when learning English can use interesting and curiosity learning methods to understand many more English vocabulary. In this study the author only uses noun vocabulary in English.The aim to be achieved in this study is to find out the causes of lack of activity of students in learning English vocabulary nouns in fourth grade elementary school and describe the use of the Bingo game method in increasing English vocabulary nouns learning activities in fourth grade elementary school. In this study it is very trying to get a picture of the application of the method of bingo games to strengthen the mastery of English vocabulary in fourth grade elementary school.Based on the results of the study there is an increase in learning activities of students in learning English vocabulary using the method of bingo games, because the method of bingo games increases understanding rather than increasing students in memorizing in English vocabulary.